Effects of ZnO nanoparticles on wastewater treatment and their removal behavior in a membrane bioreactor. (June 2015) - Tan, Magdalene; Qiu, Guanglei; Ting, Yen-Peng
Graphical abstract: Highlights: Long-term exposure of ZnO NPs caused moderate deterioration in pollutants removal. ZnO NPs altered activated sludge properties and caused higher membrane fouling. Shifts in bacteria community structure were noted but with unaffected diversity. ZnO NPs were removed effectively in MBR mainly via sludge sorption. Membrane filtration contributed significantly to ZnO NPs removal. Abstract: Long-term effects of ZnO nanoparticles on the system performance of an MBR were investigated together with their removal behavior in the system. Continuous operation over 242 days showed that ZnO NPs at both 1.0 and 10.0 mg/L caused moderate deterioration in the removal of COD, nitrogen and phosphorus. Denitrification was affected upon the exposure but recovered subsequently. Although no significant acute effect on ammonia-oxidization was observed, permanent inhibition occurred after long-term exposure. Nitrite-oxidization was not affected even with 10.0 mg/L ZnO NPs. Significant changes were observed in activated sludge properties which resulted in severe membrane fouling. Although ZnO NPs caused changes in the bacteria community structure, the diversity however remain unchanged. ZnO NPs was removed effectively in the MBR (>98%) with biosorption being a major removal mechanism. Membrane filtration also played an important role (20% of the total removal) especially at high ZnO NPs concentrations (around 10.0 mg/L).